2021
DOI: 10.1016/j.cognition.2021.104586
|View full text |Cite
|
Sign up to set email alerts
|

Early visual deprivation does not prevent the emergence of basic numerical abilities in blind children

Abstract: Studies involving congenitally blind adults demonstrated that visual experience is not a mandatory prerequisite for the emergence of efficient numerical abilities. It remains however unknown whether blind adults developed lifelong strategies to compensate for the absence of foundations vision would provide in infancy. We therefore assessed basic numerical abilities in blind and sighted children of 6 to 13 years old. We also assessed verbal and spatial working memory abilities and their relationship with mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…For example, visual receptive fields must repeatedly remap as the distance between the two eyes increases. Indeed, experience-dependent matching of stimulus selectivity of the visual input from the two eyes occurs during the critical period [ 22 ]. Changes in the microstructure of white matter tracts have been found in late-blind subjects when compared to the congenitally blind or sighted controls [ 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, visual receptive fields must repeatedly remap as the distance between the two eyes increases. Indeed, experience-dependent matching of stimulus selectivity of the visual input from the two eyes occurs during the critical period [ 22 ]. Changes in the microstructure of white matter tracts have been found in late-blind subjects when compared to the congenitally blind or sighted controls [ 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such findings increase the knowledge related to the impact of visual experience on numerical processing. Since both positive and negative numbers are fundamental aspects of learning mathematical principles, the outcomes of the present study provide information about the need to implement early rehabilitation strategies to prevent the risk of numerical difficulties in visually impaired children [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Morgan et al (2011) also find that children with speech-language impairments do not lag behind non-disabled children in their math skills growth [ 31 ]. Crollen et al (2021) have reported that blind children might even outperform their non-blind peers in numeracy abilities [ 32 ]. However, Zhang et al (2019) demonstrate that children with seeing or auditory perception challenges struggle to learn numeracy skills related to visual Arabic or verbal modules [ 33 ].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Children with vision and hearing disabilities perform well in numeracy skills return to schooling compared to non-disabled children . This hypothesis is based on earlier evidence [ 30 , 32 ], suggesting that vision and hearing abilities might not be crucial in developing numeracy skills. Although learning numeracy skills related to visual or verbal modules might be relevant [ 33 ], the numeracy tests involved in this survey are pretty basic.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…There is evidence from previous work that vision is not required to learn certain STEM concepts, and BLV individuals were able to perform at similar or higher levels than sighted populations [14], [15]. Giudice emphasizes the importance of developing spatial skills, and that the development and use of these skills can be equally as beneficial as the use of visual skills.…”
Section: Benefits Of Spatial Abilitymentioning
confidence: 99%